Subcutaneous Administration of PDGF-AA Improves the Functional Recovery After Spinal Cord Injury - Guo, Xue-Yan; Duan, Fei-Xiang; Chen, Jing; Wang, Ying; Wang, Rui; Shen, Lin; Qi, Qi; Jiang, Zhi-Quan; Zhu, An-You; Xi, Jin; Lü, He-Zuo; Hu, Jian-Guo (Frontiers in Neuroscience, 2019)
Previous studies by our group have demonstrated that the transplantation of exogenous platelet-derived growth factor (PDGF)-AA-overexpressing oligodendrocyte progenitor cells (OPCs) promotes tissue repair and recovery of neurological function in a rat model of spinal cord injury (SCI). However, it remains unclear whether treatment with PDGF-AA also affects endogenous oligodendrocytes (OL) or even neurons, thus promoting further functional recovery after SCI. In the present study, we evaluated the therapeutic potential of PDGF-AA treatment by direct injection of PDGF-AA into the injured rat spinal cord immediately after SCI. We demonstrated that PDGF-AA injection resulted in increased tissue sparing, re-myelination and functional recovery in rats following SCI. Further experimentation confirmed that PDGF-AA increased the survival of endogenous OPCs and OLs, and promoted the proliferation of OPCs and their differentiation into OLs. Moreover, PDGF-AA also protected motor neurons from death in the injured spinal cord. These results indicated that PDGF-AA administration may be an effective treatment for SCI. Keywords: Platelet-derived growth factor-AA; Subcutaneous administration; Spinal cord injury; Functional recovery; Oligodendrocytes.